Serum levels of oxidative stress, IL-8, and pepsinogen I/II ratio in Helicobacter pylori and gastric cancer patients: potential diagnostic biomarkers - Marwa Nasier-Hussain; Jaleel Najah Samanje; Khatere Mokhtari; Mohsen Nabi-Afjadi; Zeinab Fathi; Asieh Hoseini; Elham Bahreini (BMC Gastroenterology)
Abstract Background and aim Helicobacter pylori (H.pylori), a gram-negative bacterial pathogen associated with an increased risk of gastric cancer. This study investigates potential factors in the incidence of gastric cancer in patients with H.pylori, including oxidative stress, inflammatory biomarkers, serum pepsinogens (PG) of I and II, and PG-I/PG-II ratio. Methods The study comprised individuals with Helicobacter pylori (H.pylori) infection, gastric cancer patients, and healthy individuals. Biochemical parameters such as FBS (fasting blood sugar), lipid profile, and liver and kidney functional factors were evaluated using colorimetric techniques. Oxidative markers such as total oxidant status (TOS) and malondialdehyde (MDA) were quantified through colorimetric methods. IL-8, PG-II, and PG-II levels were also determined using the ELISA technique. Results Individuals with H. pylori infection exhibited elevated levels of IL-8 (940.5 ± 249.7 vs. 603.4 ± 89.1 pg/ml, P < 0.0001) and oxidative species (5.47 ± 0.7 vs. 1.64 ± 0.7 nM, P < 0.05) compared to gastric cancer patients, who, despite having lower levels of IL-8 and oxidative species, showed higher levels of MDA. H.pylori patients exhibited significantly higher levels of PG-I (7.28 ± 2.1 vs. 2.61 ± 1.4 ng/ml, P < 0.001), PG-II (3.21 ± 1 vs. 2.6 ± 0.6 ng/ml, P < 0.001), and the PG-I/PG-II ratio (2.27 ± 1.2 vs. 1 ± 0.4, P < 0.001) compared to gastric cancer patients. The findings were substantiated using various data analysis platforms such as Gene Expression Profiling Interactive Analysis (GEPIA), UALCAN (The University of ALabama at Birmingham CANcer data analysis), cBioPortal, and TIMER (Tumor IMmune Estimation Resource). These parameters could serve as potential diagnostic biomarkers for screening and therapeutic interventions based on the cut-off values derived from ROC (receiver operating characteristic) curves for IL-8, PGI, PGII, and PGI/PGII across the three groups. Conclusions IL-8, PGI, PGII, and PGI/PGII parameters could serve as potential diagnostic markers for the screening and treatment of gastric conditions.